2012
DOI: 10.1634/theoncologist.2012-0051
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Vitamin D Supplementation During Androgen Deprivation Therapy for Prostate Cancer: A Critical Review

Abstract: After completing this course, the reader will be able to:1. Describe the prevalence of bone loss with androgen deprivation therapy for prostate cancer.2. Discuss the possible increased risk of cardiovascular disease and of advanced prostate cancer with high calcium intake.This article is available for continuing medical education credit at CME.TheOncologist.com. CME CME ABSTRACTBackground. Loss of bone mineral density is an unintended consequence of androgen deprivation therapy in men with prostate cancer. Sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 81 publications
0
42
0
2
Order By: Relevance
“…A similar survey has not been conducted within the Australian medical system. Therefore, despite various guidelines [247] and suggested benefits [56,247,253,[284][285][286][287] , men treated with ADT are not commonly supplemented with calcium and vitamin D and deficiencies are highly prevalent [249,250] .…”
Section: The Role Of Nutritional Supplementation On Muscle Fat and Pmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar survey has not been conducted within the Australian medical system. Therefore, despite various guidelines [247] and suggested benefits [56,247,253,[284][285][286][287] , men treated with ADT are not commonly supplemented with calcium and vitamin D and deficiencies are highly prevalent [249,250] .…”
Section: The Role Of Nutritional Supplementation On Muscle Fat and Pmentioning
confidence: 99%
“…Due to current practice guidelines [247] and a pilot study conducted in 31 men undergoing ADT for PCa in which 65% reported taking vitamin D supplementation (90% at least 1,000 IU/day), all men randomised to usual care received 1,000 IU vitamin D per day.…”
Section: Usual Care Control Groupmentioning
confidence: 99%
“…In Manchester, UK, 13 minutes exposure of 35% body surface to midday sun in June is sufficient to achieve satisfactory vitamin D status (Rhodes et al, 2010). In a study in winter and spring in Denmark, exposure of the hands and face to solar outdoor UV did not induce vitamin D production before the month of May (Datta et al, 2012). It is a matter of debate which summertime vitamin D levels are sufficient to maintain adequate levels in winter and early spring.…”
Section: Vitamin Dmentioning
confidence: 99%
“…Beyond fracture risk assessment, both lifestyle (smoking cessation, moderating alcohol intake, and regular exercises) and pharmacological (calcium, vitamin D) interventions have been recommended to help prevent bone loss and optimize bone health [16, 21,25] regardless of fracture risk. In men with high fracture risk, antiresorptive therapy (e.g., bisphosphonates) is also recommended [21,24].…”
Section: Optimizing Bone Health In Men Receiving Adtmentioning
confidence: 99%